Capacity Building Pedagang Pasar Kolombo Sleman Menggunakan Aplikasi Edukasi Hybrid Sepasar - Santosa, Awan; Tri harsini Wahyuningsih; Sumiyarsih; Sri handayani (Masyarakat Berdaya dan Inovasi, 2023)
Kolombo Market is the one of the traditional market in Sleman, Yogyakarta.. Kolombo Market is one of the markets affected by the online market. Based on these problems, the solution is the Sepasar application as a Hybrid Education and Online Marketing media. Sepasar as a solution to the problems faced by providing online courses according to the needs of Kolombo market traders . The Sepasar application also helps increase sales for Kolombo Market Merchants by promoting products, events, and services. Expected output targets from the joint community empowerment program Sepasar is existence enhancement knowledge, skills , HR and organizational capacity, as well as digital literacy of Kolombo market traders in using various digital media that help them in marketing, finance and organizational management .